If f(x,y,z) = f(x,y) g(y) h(z), find Fxyz The question is regarding partial differentiation. I tried doing it and managed to obtain fxgyhz. Is this the way to simplify the answer ?
Follow Math Help Forum on Facebook and Google+
Hmm. I don't think you've managed to take the y derivative properly. You have two functions of y multiplied together, so you'll have to use the product rule.
Would I get the following:
Fx = fx(x,y) g(y) h (z)
Fxy = [fx(x,y) gy + fxy(x,y) g(y)]h(z)
Fxyz = [fx(x,y) gy + fxy(x,y) g(y)]hz
That looks good to me!
View Tag Cloud